IMPROVING STUDENT LEARNING OUTCOMES USING MAKE A MATCH LEARNING MODEL IN IPS STUDENTS IN VOCATIONAL SCHOOL, Va SD INPRES BALIASE, MARAWOLA DISTRICT - Novi M Mannassai; Rizal Rizal (Jurnal Dikdas, 2022)
The problem in this study is the low student learning outcomes in social studies subjects. Lack of student understanding in understanding learning material. The classroom action research using the Make a Match model aims to improve the learning outcomes of Social Studies in Va. Inpres Baliase Elementary School, Marawola District. The subjects of this study were students of Va. Inpres Baliase Elementary School, Marawola Subdistrict, with 20 students consisting of 9 male students and 11 female students enrolled in the academic year 2020/2021. This study consisted of two cycles, in each cycle two meetings were held. Each cycle consists of four stages, namely: 1) action planning, 2) action implementation, 3) observation, 4) reflection. The results showed that in pre-action the percentage of classical learning completeness (KBK) was obtained by 10% and in the first cycle the percentage of classical learning completeness (KBK) was obtained by 50%. While in the second cycle the percentage of classical learning completeness (KBK) is obtained by 85%. Based on the percentage of completeness of learning outcomes in cycle I and cycle II, there has been a significant increase in the CBC of 35%, from the first cycle of 50% and the second cycle of 85%. Based on these results it can be concluded that by applying the Make a Match type of cooperative learning model can improve the learning outcomes of students of the Va Inpres Baliase SD Class in social studies subjects.